ANALYSIS OF MATHEMATICAL PROBLEM SOLVING SKILLS ON THE RELATIONSHIP AND FUNCTION MATERIAL OF GRADE VIII STUDENTS OF SMPN 6 PALU - Rahim, Nur Mei Sakin; Nurhayadi, Nurhayadi; Rizal, Muh; Idris, Mustamin (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research aims to describe the mathematical problem solving abilities in relation and function material for class VIII students at SMP Negeri 6 Palu. This type of research is qualitative research. The research subjects were three students from 32 class VIII F students. Students were grouped into three categories, namely high ability students, medium ability students and low ability students. Each category is represented by one student. The results of this research are (1) Subjects with high abilities can understand problems, plan solutions, solve problems but the subjects do not carry out re-examination. (2) Subjects with moderate abilities can understand the problem, are still lacking in planning solutions, cannot solve the problem and the subject cannot carry out re-examination. (3) Subjects with low abilities cannot fulfill all the problem solving indicators used in the research.